Maternal Photoperiodic Programming: Melatonin and Seasonal Synchronization Before Birth - van Dalum, Jayme; Melum, Vebjørn J.; Wood, Shona H.; Hazlerigg, David G. (Frontiers in Endocrinology, 2020)
This mini-review considers the phenomenon of maternal photoperiodic programming (MPP). In order to match neonatal development to environmental conditions at the time of birth, mammals use melatonin produced by the maternal pineal gland as a transplacental signal representing ambient photoperiod. Melatonin acts via receptors in the foetal pituitary gland, exerting actions on the developing medio-basal hypothalamus. Within this structure, a central role for specialised ependymal cells known as tanycytes has emerged, linking melatonin to control of hypothalamic thyroid metabolism and in turn to pup development. This review summarises current knowledge of this programming mechanism, and its relevance in an eco-evolutionary context. Maternal photoperiodic programming emerges as a useful paradigm for understanding how in utero programing of hypothalamic function leads to life-long effects on growth, reproduction, health and disease in mammals, including humans.